Tense as a Grammatical Cohesive Device in the Performance of Iraqi EFL University Students in the Area of Narrative Texts (Journal of the College of Basic Education, 2022)
The present paper focuses on use of tense as a cohesive devices and its role in keeping the coherence of a written text. Cohesion is an attempt to create a meaningful discourse in general and tense as a grammatical product is one of the basic constraints that leads to achieve cohesion. The correct use of tense explains why a succession of sentences is meaningful discourse and not a disconnected text . The former use of the verb in one sentence can limit the later choice of the verb in the next . The EFL university students have many difficulties in writing effective cohesive text in general and in using appropriate tense in particular, they tend to make improper shift in tense particularly in writing narrative text which requires to use the correct form of the verb in order to illustrate an event. The data was collect from the student performance of writing a narrative text and analysed to verify the hypothesis .The results of verifying the collected data lead to conclusions among which that there is a significantly misuse of proper tense and There is a serious difficulty in shifting from past tense to future tense, learner’s use of inappropriate tense is more than the appropriate one.